2012
DOI: 10.5812/numonthly.3528
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Screening for Detection of Renal Abnormalities in Asymptomatic School Children

Abstract: BackgroundUrinary screening tests for early detection of renal diseases in asymptomatic school children and adolescents are important in the detection of silent renal diseases.ObjectivesThe purpose of the study was to determine the prevalence of occult renal diseases by dipstick test (reagent strips) in asymptomatic Nepalese children.Patients and MethodsA total of 2,243 school children, aged 5–15 years, were screened for urinary abnormalities using dipstick test screening. The children who tested positive in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
4
16
3
Order By: Relevance
“…In addition, the prevalence of proteinuria and/or hematuria may be related to different age groups. The findings of the current study were consistent with those of Parakh et al who found that urinary abnormalities were more common in girls than boys (12). Other authors (21-23) also showed that urinary abnormalities were more frequent in girls compared with boys.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, the prevalence of proteinuria and/or hematuria may be related to different age groups. The findings of the current study were consistent with those of Parakh et al who found that urinary abnormalities were more common in girls than boys (12). Other authors (21-23) also showed that urinary abnormalities were more frequent in girls compared with boys.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of urine abnormality persisted in 0.79% on further testing in the second screening. It is compatible with the results of other studies that showed a prevalence of 0.72% and 0.71%, respectively (11,12). Proteinuria is relatively common in children, with a reported prevalence of 1%-10%, while persistent proteinuria is much less common (13).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Data describing the spectrum of renal diseases in hospitalized children in our neighbouring country Nepal is scanty 6 . Previously, the prevalence of renal diseases in asymptomatic school children was found to be 0.71% in our country 7 .…”
Section: Introduction:-mentioning
confidence: 74%
“…Variations in prevalences of proteinuria were associated with varying racial backgrounds. 39 HIVAN was not only found to be more common in the African races, but families of HIVAN patients had higher incidence of kidney disease. 40 However, some studies did not include a family history of kidney disease as one of the variables.…”
Section: Discussionmentioning
confidence: 99%